LA FOI COMME PASSION ET ADHESION : UN PARADOXE ABSOLU DANS LA PENSEE DE SOREN KIERKEGAARD - Kombozi Mokili, Jean-Pierre; Baelongandi, Augustin Sombo; Matuka Embolu, Jean-Médard (IJRDO - Journal of Business Management, 2021)
The man’s utilitarian conception is sustained by the men, who have sought-after qualities. The sciences even go as far as writing the man’s theories ready to the manipulation or even his judgment. These attitudes send back us to the critique that Soren Kierkegaard had formulated against the faith. What imports thus in Christianity is not to understand but to live according to all his requirements and in the fullness of his sense. Whatever he doesn’t sustain the subjectivism, by his demands, he wants to put in relief the value that is" individual ". He finds in Christianity the source of his demand. The problematic of our investigating, driven us to know what it is the faith, as passion and adherence in the philosophy of Kierkegaard. This last consists of the faith, here that that in his way, Hegel with a lot of exactness, name the interior certainty, that anticipates the infinity. The faith has his own rationality of that the reason will never consist. It is what the absolute paradox of Kierkegaard founds. Kierkegaard has the merit to have inaugurated a reflection fascinated on the existing and to his situation in the world. Of the different treaties on the anguish, the despair, guilt, main existential dramas that it exhumed, gave back a new breath to the philosophical reflection.